TEACHING PROGRAMMING AS A KEY COMPETENCE OF A MODERN STUDENT - Gulomov Shavkat Makhmudovich (International Scientific and Current Research Conferences, 2023)
The article examines the importance of learning programming in modern education and the role of this skill as a key competence for students. The authors emphasize that in the context of the digital transformation of society, the ability to program becomes an essential element of professional training. The article discusses the benefits of mastering programming skills, including the development of logical thinking, creativity and problem-solving abilities. Methods and approaches to the implementation of programming training in educational programs are also considered, as well as recommendations for the effective implementation of this process are put forward. In conclusion, the article emphasizes the need for attention to the formation of programming skills among students as a strategic direction of modern education.